A Innovative Approaches: SWOT Analysis of Balinese Souvenir Marketing in Sukawati Market During and After the Pandemi - Ketut Witara; Ririn Andriana; Dodit Cahyo Nugroho (Fakultas Ekonomi Universitas Warmadewa, 2024)
The COVID-19 pandemic has significantly impacted the tourism sector in Bali, including the sales of Bali's typical souvenirs at Pasar Sukawati Gianyar. This study aims to analyze the marketing strategy of Bali's typical souvenirs at Pasar Sukawati Gianyar using SWOT analysis during the COVID-19 pandemic. This research used a qualitative method with in-depth interviews with five Bali's typical souvenirs traders at Pasar Sukawati Gianyar. The results showed that the strengths of the marketing strategy of Bali's typical souvenirs at Pasar Sukawati Gianyar during the pandemic are good product quality and competitive prices. The weaknesses of the marketing strategy are a lack of innovation and a lack of online product promotion. The opportunities of the marketing strategy are to increase the use of digital platforms to promote products and develop new products. The threats of the marketing strategy are strong competition from online souvenir markets and a decrease in the number of visitors to the market during the pandemic. Therefore, Bali's typical souvenirs traders at Pasar Sukawati Gianyar need to optimize strengths and opportunities, as well as overcome weaknesses and threats by innovating and improving online promotion. This study contributes to understanding the marketing strategy of Bali's typical souvenirs in traditional markets during the COVID-19 pandemic and provides recommendations to address the issues faced by Bali's typical souvenirs traders at Pasar Sukawati Gianyar.